2017
DOI: 10.1186/s12872-017-0499-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of a home-based cardiac rehabilitation programme of mixed surveillance in patients with ischemic heart disease at moderate cardiovascular risk: A randomised, controlled clinical trial

Abstract: BackgroundPrevious studies have documented the feasibility of home-based cardiac rehabilitation programmes in low-risk patients with ischemic heart disease, but a similar solution needs to be found for patients at moderate cardiovascular risk. The objective of this study was to analyse the effectiveness and safety of a home-based cardiac rehabilitation programme of mixed surveillance in patients with ischemic cardiopathology at moderate cardiovascular risk.MethodsA randomised, controlled clinical trial was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
183
2
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(204 citation statements)
references
References 37 publications
4
183
2
15
Order By: Relevance
“…In a cohort with ischemic CVD at moderate risk, one RCT found no significant differences between the traditional CR with mixed surveillance, and home-based tele-CR when it came to ET time, energy expenditure, and heart rate (HR) recovery in the first minute after exercise testing; however, HRQoL scores were higher in the conventional group. 30 Hwang et al enrolled 53 participants with HF into either home-based or conventional CR and found no significant difference with respect to the 6-minute-walk performance test. 31 Similarly, Moholdt and colleagues evaluated differences in oxygen (O2) uptake and HRQoL between facility-based and home-based CR and found no difference between groups in either O2 uptake and HRQoL.…”
Section: Modes Of Delivering Etmentioning
confidence: 99%
“…In a cohort with ischemic CVD at moderate risk, one RCT found no significant differences between the traditional CR with mixed surveillance, and home-based tele-CR when it came to ET time, energy expenditure, and heart rate (HR) recovery in the first minute after exercise testing; however, HRQoL scores were higher in the conventional group. 30 Hwang et al enrolled 53 participants with HF into either home-based or conventional CR and found no significant difference with respect to the 6-minute-walk performance test. 31 Similarly, Moholdt and colleagues evaluated differences in oxygen (O2) uptake and HRQoL between facility-based and home-based CR and found no difference between groups in either O2 uptake and HRQoL.…”
Section: Modes Of Delivering Etmentioning
confidence: 99%
“…The platform is Conformité Européenne certified as a medical device for use in the European Union. It has been tested in patients who have undergone an exercise echocardiography test [3] and cardiac rehabilitation [6].…”
Section: Ecg Platformmentioning
confidence: 99%
“…Several reports have been published, in which wearable devices achieved very positive results with high diagnostic accuracy [3][4][5][6]. It was demonstrated that a garment-inserted electrocardiography (ECG) system can obtain similar results to those achieved with the conventional treadmill system during exercise testing,which may also include obtaining echocardiographic images [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations